Analisis Wacana Kritis Pemberitaan BRICS Dalam Media CNN Arabic 2023-2024 - Dinda Fitrianda; Fatimah Dhea Alyfiah; Nasution, Anisah Mai; Suri, Nursukma (Institut Muslim Cendekia, 2025)
This study examines the framing of BRICS-related news by CNN Arabic during the 2023–2024 period amid the bloc’s increasing role in global economic and geopolitical dynamics. This research is significant because the media play a strategic role in shaping public perception in the Arab region regarding shifts in international power. The study aims to identify the representation of BRICS in CNN Arabic’s news discourse using Teun A. van Dijk’s Critical Discourse Analysis model, which includes macrostructure, superstructure, and microstructure. The research employs a qualitative descriptive method through library research by analyzing CNN Arabic news texts related to global economic issues, political statements, and the expansion of BRICS membership. The findings indicate that CNN Arabic represents BRICS as an alternative global actor capable of balancing Western economic dominance, as reflected through lexical choices and discourse structures that emphasize cooperation, stability, and strategic influence. The novelty of this study lies in its focus on the representation of BRICS in Arab media, which remains relatively underexplored. These findings imply the importance of more critical and balanced media policies in presenting global geopolitical issues.